Kelas Acting in Animation Class untuk Mahasiswa Animasi - Arby, Sella Putri (ULTIMART Jurnal Komunikasi Visual, 2024)
This research aims to investigate the impact of Acting in Animation course and how it helps animation students develop their ability to use movements and facial expressions to tell a story through 3D character animation models. The main focus of this research is to see if animation students can animate 3D character models better after understanding movements and emotions in acting techniques. This research will analyze the influence of body movements, facial expressions, and even vocal expressions on the overall quality of an animated work. The research method involves an in-depth study of acting for animators theories based on 12 animation principles. Through interviews with experienced animators, direct observation of the animation process, and critical analysis of prominent animation works, this research aims to identify the most effective acting strategies and techniques for creating convincing animated characters. The result of this research is expected to provide a deeper insight into the needs of acting for animation production, as well as provide practical guidance for animation students who wants to improve their abilities as animators to create the proper module in Acting in Animation class. Keywords: animation; acting; students; animators